Treatment‐Resistant Depression and Risk of Suicide. Issue 4 (20th March 2013) - Pfeiffer, Paul N.; Kim, Hyungjin M.; Ganoczy, Dara; Zivin, Kara; Valenstein, Marcia
Abstract : We evaluated whether treatment‐resistant depression (TRD) as measured by the Massachusetts General Hospital (MGH) staging method was associated with suicide in a large U.S. health system. Data from the Veterans Health Administration and the National Death Index were used to conduct a case–control study of patients newly diagnosed with depression who received antidepressant treatment between 2003 and 2006. Suicide cases ( N  = 499) were matched with nonsuicide controls ( N  = 1994). Conditional logistic regression was used to assess whether MGH stage at time of suicide (or matched date) was associated with case status, adjusting for patient demographic characteristics, comorbidity, and service use. Results indicated 11.6% of suicide cases had MGH stage 3 or greater (indicating at least two antidepressant trials) compared to 6.4% of controls ( p  < .001). In adjusted analyses, suicide was not significantly more likely among patients with stage 3 or greater (OR 1.52; 95% CI: 0.98, 2.37) or stages 1.5–2.5 (OR 1.19; 95% CI: 0.91, 1.55) compared to patients with stage 1 or less (<10 weeks of antidepressant medication). Staging TRD using MGH criteria is unlikely to substantially improve suicide risk assessment of depressed patients beyond existing measures contained in health system records.